Effect of an exercise program for posture correction on musculoskeletal pain - Kim, DeokJu (J Phys Ther Sci, 2015)
[Purpose] The present study investigated the effect of an exercise program for posture correction on musculoskeletal pain. [Subjects] Between September 2, 2013 and November 3, 2013, an exercise program was performed in 88 students from S University in K city (male students, n = 34; female students, n = 54). [Methods] The exercise program for posture correction was performed for 20 minutes per session, 3 times a week for 8 weeks. Pain levels were measured using a pain scale, and pain levels before and after the exercise program were compared. [Results] Overall, pain levels of the participants were lower after the exercise program than before the program, and significant differences in pain levels were noted in the shoulders, middle back, and lower back. [Conclusion] In conclusion, shoulder pain, mid back pain, and low back pain were relieved with the exercise program for posture correction. Therefore, the findings of this study can be used to improve the work efficiency of students as well as people engaged in sedentary work.